IMPLEMENTASI NILAI-NILAI SYARIAH DALAM PELAYANAN PEMBIAYAAN PERUMAHAN Kajian Fenomenologis pada BTN Syariah Solo : Kajian Fenomenologis pada BTN Syariah Solo - Hisyam Mubarok; Agus Marimin; Sumadi (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the implementation of Sharia values in housing financing services at BTN Syariah Solo using a phenomenological approach. The research employed a qualitative, phenomenological design to understand the experiences and meanings constructed by customers and employees regarding Islamic housing financing services. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Moustakas’ phenomenological framework, including epoche, horizontalization, clustering themes, textural description, and structural description. The findings reveal that the implementation of Sharia values is reflected in the use of Sharia-compliant contracts, supervision by the Sharia Supervisory Board (DPS), transparent information practices, and service practices grounded in honesty and justice. The phenomenological findings indicate that customers perceive Islamic housing financing not merely as a means of acquiring a house but also as a way to attain inner peace (tuma’ninah) and blessings in family life. However, limited Islamic financial literacy remains a challenge, as some customers still struggle to distinguish between profit margins and conventional interest. Furthermore, service digitalization has been perceived as an important factor in enhancing transparency, accountability, and customer trust in Islamic banking institutions. This study highlights that the success of Islamic service delivery is determined not only by compliance with Sharia regulations and contracts but also by the institution’s ability to provide spiritual, educational, and social benefits that customers genuinely experience.